Pengaruh Motivasi, Pelatihan Dan Penghargaan Terhadap Kinerja Karyawan Pada Pt Duta Niaga Logistik Di Batam - Harianja, Josepin (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2023)
This study aims to examine and analyze the effect of motivation, training and rewards on employee performance. The population of this study is employees, amounting to 150 people. A sample of 109 employees uses the Slovin formula in sampling. The analysis technique used is t-test and F-test. The results of this study prove that: The t-value of motivation is 3.057 with a significant level of 0.011 (alpha <0.05). Ha is accepted and H0 is rejected or motivation partially affects employee performance. The calculated t value for training is 5.457 with a significant level of 0.000 (alpha <0.05). Ha is accepted and H0 is rejected or training partially affects employee performance. The t value for the award is 2.103 with a significant level of 0.038 (alpha <0.05). Ha is accepted and H0 is rejected or work training partially affects employee performance. Based on the beta value, it is known that (X1, X2, X3) which has the most dominant effect on employee performance is training (X2) with a beta value of 0.492 or 49.2%. From the F test, the independent variables X1, X2, and X3 were counted as 253.535 with a significant level of 0.000. This significant value is smaller than alpha 0.05 which indicates that Ha is accepted and H0 is rejected which means that motivation (X1), training (X2), and appreciation (X3) simultaneously or jointly have a positive and significant influence on employee performance (Y).